2012
DOI: 10.1136/flgastro-2012-100176
|View full text |Cite
|
Sign up to set email alerts
|

Should patients expect their colonoscopy to reach the standards experienced by bowel cancer screening patients?

Abstract: OPINION 122Although the administrative burden of the endoscopy quality improvement programme is immense, these measures have undoubtedly had a very positive impact on patient-centred endoscopic care in the UK.The first large UK audit of colonoscopy standards undertaken by Bowles et al revealed a caecal intubation rate (CIR) of only 56.9% from 9223 procedures. 1 The potential implications of this poor national performance were significant. One of the most important indications for colonoscopy is to prevent colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This may overestimate the effectiveness of the procedure, as studies have shown that this proportion can be lower. 52,53 Finally, recent evidence has shown an increase in the incidence of CRC in European adults younger than 50 y. 54 The model presented here does not represent such trends in CRC incidence and so may underestimate the potential benefits of policies that offer earlier start ages as a tradeoff against higher screening frequency.…”
Section: Discussionmentioning
confidence: 90%
“…This may overestimate the effectiveness of the procedure, as studies have shown that this proportion can be lower. 52,53 Finally, recent evidence has shown an increase in the incidence of CRC in European adults younger than 50 y. 54 The model presented here does not represent such trends in CRC incidence and so may underestimate the potential benefits of policies that offer earlier start ages as a tradeoff against higher screening frequency.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, the model assumes 95% of colonoscopies reach the caecum. This may overestimate the effectiveness of the procedure as studies have shown that this can be lower[46,47]. Despite these simplifications, we are confident that the analysis valuably illustrates the relevance of considering a broad range of policy alternatives and a clear indication of how a national bowel cancer screening programme could save more lives.…”
Section: Discussionmentioning
confidence: 96%